2021
DOI: 10.11591/ijeecs.v24.i3.pp1789-1795
|View full text |Cite
|
Sign up to set email alerts
|

Rimigs: the impact of gamification on students’ motivation and performance in programming class

Abstract: Gamification is described as the art of changing human activity to a game-like environment to gain user engagement. Rimigs is a developed gamification system discussed in this research and was built based on Octalysis framework. This research aims to design and identify the impact of using a gamification system on students’ motivation and performance, especially in programming classes. Through Rimigs, students’ engagement and performance can be enhanced by freely choosing tasks or quests according to the rank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Dalam konteks metode pembelajaran e-learning, penerapan gamifikasi memberikan wawasan tentang tantangan dan arah masa depan di bidang ini, khususnya dalam konteks ilmu kompute. Selain itu, penelitian yang dilakukan dan menyajikan kerangka konseptual dan model penerapan gamifikasi di kelas e-learning dan pemrograman, menyoroti potensi gamifikasi untuk mengubah pengalaman pembelajaran online dan meningkatkan motivasi dan kinerja siswa (Pratama et al, 2021).…”
Section: Gamifikasi DI Bidang Pendidikanunclassified

Gamification Developments in Education

Aris Triwahyu Febriansah,
Syaifuddin,
Yerry Soepriyanto
2024
Scholaria
“…Dalam konteks metode pembelajaran e-learning, penerapan gamifikasi memberikan wawasan tentang tantangan dan arah masa depan di bidang ini, khususnya dalam konteks ilmu kompute. Selain itu, penelitian yang dilakukan dan menyajikan kerangka konseptual dan model penerapan gamifikasi di kelas e-learning dan pemrograman, menyoroti potensi gamifikasi untuk mengubah pengalaman pembelajaran online dan meningkatkan motivasi dan kinerja siswa (Pratama et al, 2021).…”
Section: Gamifikasi DI Bidang Pendidikanunclassified

Gamification Developments in Education

Aris Triwahyu Febriansah,
Syaifuddin,
Yerry Soepriyanto
2024
Scholaria
“…Gamification approach can also improve learning and social interactions as students need to collaborate with other players in completing the structured tasks [8], [13]. Apart from making learning more interesting, gamification approach also promotes students to be more motivated to participate in the game and it enhances their cognitive growth, such as factual knowledge [14], increase problem-solving skills and ability to apply concepts and principles [10], [15]. Games have the potential to excite students' interest in content as well as engage them in classroom discussion [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some students consider programming to be a challenging subject to study [1], [2]. While several studies have identified various issues with programming learning, the learning environment in programming classes influences students" motivation and performance in learning [3], [4]. Other issues that students face include conceptual understanding [5], code quality [6] and a tedious learning process [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Gamification is the application of game mechanics and activities to an environment where the primary goal is not entertainment [12]. It has been used extensively in education with positive results [4], [11]- [14].…”
Section: Introductionmentioning
confidence: 99%